Type specimens of Chrysomelidae and Megalopodidae (Coleoptera) in the National Forest Insect Collection (NFIC), Forest Research Institute, Dehra Dun, India - Faisal, Mohammad; Singh, Sudhir (Zootaxa, 2018)
Type specimens of 28 species of Chrysomelidae and one of Megalopodidae present in National Forest Insect Collection (NFIC), Forest Research Institute (FRI), Dehra Dun (India) are digitized. Information such as label data, original citations, photographs of specimens from dorsal side, and condition of specimens are provided. These types (4 primary and 25 secondary) belong to 20 genera, i.e. 19 in 12 tribes of 5 subfamilies of Chrysomelidae—Bruchinae (Spermophagus atroapicalis Pic, S. notatipennis Pic, S. uniformis Pic, Bruchus bilineatopygus Pic, B. gardneri Pic, B. albocallosus Pic, and B. maculatithorax Pic), Cassidinae (Callispa almora Maulik, Downesia sasthi Maulik Estigmena bicolor Bhasin, and Platypria garthwaitei Bhasin), Cryptocephalinae (Aetheomorpha coorgensis Bryant, Aspidolopha nigrocurvilinea Bryant, A. ornaticollis Bryant, Chlamys padmanabhai Bhasin, C. travancorensis Bhasin, Exema fulvitarsis Bryant, E. salemensis Bhasin, Melixanthus coorgensis Bryant, and Gynandrophthalma flaviventris Bryant), Eumolpinae (Trichotheca beesoni Bryant), Galerucinae (Chaetocnema merguiensis Bryant, Diorhabda trirakha Maulik, Elytropachys sandalensis Bryant, Longitarsus cyanipennis Bryant, L. taklechensis Bryant, Podagrica apicefulva Bryant and Sastra mamaya Maulik), and one in Megalopodidae Megalopodinae (Temnaspis quadriplagiatus Bryant).